The geology of the Kalahari Gemsbok National Park - S. J Malherbe (Koedoe: African Protected Area Conservation and Science, 1984)
The floor rocks of the Kalahari Group are only known from boreholes. It consists of rocks of the Karoo Sequence with its associated intrusions of dolerite. The pre-Kalahari topography was dissected by rivers which drained in the direction of the present Botswana. The distribution of the oldest formation of the Kalahari Group, the Wessels Formation (clayey gravel), and the overlying Budin Formation (clay) was also determined from borehole records. The Karoo Sequence was probably the source of these rocks. The overlying Eden Formation (sandstone, grit and conglomerate) had a source which could yield much sand. All these formations were deposited under fluviatile conditions. The Mokalanen Formation (calcrete) and the Gordonia Formation (sand) indicate a change from a humid to an arid environment. The Lonely Formation (clayey diatomaceous limestone) was deposited in a lacustrine environment. It also indicates a higher rainfall in an otherwise arid period. The Goeboe Goeboe Formation consists of clay and sand in the pans and rivers.